Albumin-encapsulated HSP90-PROTAC BP3 nanoparticles not only retain protein degradation ability but also enhance the antitumour activity of BP3 in vivo. (21st April 2023) - Jiang, Qingna; Hu, Yan; Liu, Quanyu; Tang, Yuanling; Wu, Xinhua; Liu, Jingwen; Tu, Guihui; Li, Ge; Lin, Xiaoqing; Qu, Minghui; Cai, Yajuan; Huang, Xiuwang; et al.
Abstract: Proteolysis-targeting chimaera (PROTAC) has received extensive attention in industry. However, there are still some limitations that hinder its further development. In a previous study, our group first demonstrated that the HSP90 degrader BP3 synthesised by the principle of PROTACs showed therapeutic potential for cancer. However, its application was hindered by its high molecular weight and water insolubility. Herein, we aimed to improve these properties of HSP90-PROTAC BP3 by encapsulating it into human serum albumin nanoparticles (BP3@HSA NPs). The results demonstrated that BP3@HSA NPs showed a uniform spherical shape with a size of 141.01 ± 1.07 nm and polydispersity index < 0.2; moreover, BP3@HSA NPs were more readily taken up by breast cancer cells and had a stronger inhibitory effect in vitro than free BP3. BP3@HSA NPs also demonstrated the ability to degrade HSP90. Mechanistically, the improved inhibitory effect of BP3@HSA NPs on breast cancer cells was related to its stronger ability to induce cell cycle arrest and apoptosis. Furthermore, BP3@HSA NPs improved PK properties and showed stronger tumour suppression in mice. Taken together, this study demonstrated that hydrophobic HSP90-PROTAC BP3 nanoparticles encapsulated by human serum albumin could improve the safety and antitumour efficacy of BP3.